Social media content in civil litigation: notorious facts about which information is publicly available - Rabczuk, Stanisław (The Opole Studies in Administration and Law, 2020)
The Act of 4 July 2019 amending the Act of Code of Civil Procedure and certain other acts has introduced a new category of common knowledge facts into the Code of Civil Procedure – facts about which information is publicly available. In accordance with the intention of the legislator, this new category of facts, in principle, includes information published on the Internet. The activity of Poles in social media, as well as the usage of social media evidence in the United States leads to the conclusion that also in Polish civil trial it may be expedient to use facts originating from social media. Therefore, the author discusses the potential use of social media in a civil trial within the framework of the institution of commonly available facts, basing his considerations in the context of the jurisprudence to date and the position of the doctrine regarding the legal institution in question.